2013
DOI: 10.1189/jlb.0113035
|View full text |Cite
|
Sign up to set email alerts
|

Mouse neutrophils express the decoy type 2 interleukin-1 receptor (IL-1R2) constitutively and in acute inflammatory conditions

Abstract: The proinflammatory activities of IL-1 are tightly controlled at different levels. IL-1R2 acts as a decoy receptor and has been shown to regulate the biological effects of IL-1 in vitro and in vivo. However, little is known about its natural expression in the mouse in physiologic and pathologic conditions. In this study, we examined IL-1R2 mRNA and protein expression in isolated cells and tissues in response to different stimulatory conditions. Data obtained using ex vivo CD11b(+)Ly6G(+) peripheral blood cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 56 publications
3
58
1
Order By: Relevance
“…We found that IL-1R2 is expressed most prominently in neutrophils among T cells, B cells, monocytes, BMMPs, and FLSCs, consistent with a recent report (47 (48) showed that neutrophils purified by the Percoll gradient method, which was used in the previous report (13), were contaminated with other types of cells, and neutrophils were indirectly activated by IL-1 through these contaminated cells.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that IL-1R2 is expressed most prominently in neutrophils among T cells, B cells, monocytes, BMMPs, and FLSCs, consistent with a recent report (47 (48) showed that neutrophils purified by the Percoll gradient method, which was used in the previous report (13), were contaminated with other types of cells, and neutrophils were indirectly activated by IL-1 through these contaminated cells.…”
Section: Discussionsupporting
confidence: 91%
“…Nonetheless, high expression of IL-1R2 in neutrophils may play some physiological and/or pathological roles. In fact, it was demonstrated that neutrophils scavenge IL-1b through IL-1R2 (49), and both human and mouse neutrophils cleave IL-1R2 to release the extracellular domain of IL-1R2 (47,50). Because an IL-1R2-expressing T cell line can neutralize IL-1 activity through IL-1R2-mediated internalization of IL-1b, but less efficiently through binding of soluble IL-1R2 to IL-1 (51), we examined the IL-1-neutralizing capacity of neutrophils in two models.…”
Section: Discussionmentioning
confidence: 99%
“…8A), leading us to investigate potential direct effects of IL-33 on myeloid cells in BMG cultures in vitro (51). Stimulation of BM cells isolated from adult WT C57BL/6 mice with rmIL-33 significantly enhanced cell proliferation during the first 2 d of culture (Fig.…”
Section: Effects Of Il-33 On Cultured Bm Cellsmentioning
confidence: 99%
“…BM-derived granulocytes (BMGs) were cultured as previously described (51). For proliferation assays, 2 3 10 5 cells/well were cultured in 96-well plates with or without G-CSF (5 ng/ml) and rmIL-33 (100 ng/ml) for indicated times before lysis in culture medium containing 1% Triton-X100 for LDH assays (Cytotoxicity Detection Kit; Roche Diagnostics, Rotkreuz, Switzerland).…”
Section: Cell Culturementioning
confidence: 99%
“…Of note, IL-1R2 binds to IL-1 with a higher affinity than to IL-1Ra, thus further enhancing the inhibitory activity of IL-1Ra (6). In contrast to the ubiquitously expressed IL-1R1, the expression of IL-1R2 is rather restricted with neutrophils being the major source in the mouse (7).…”
mentioning
confidence: 96%